(untitled) (Fiep Bulletin - online, 2014)
The aging process in the population has been accelerating, and there is a concern about professionals’ performance who works in the superior education. The objective of this descriptive and exploration study it was to analyze the expectations of professors in physical education course related to personal aging process. The instrument used to measure was a half-structuralized interview, composed for 13 questions destined to the characterization of the sample and expectations related to the aging; the sample was composed by no-probabilistic intentional sample, with 44 professors, 28 of masculine gender and 16 of feminine one, with average of age of 40,6 years, and most of them were married, and graduated in Physical Education and with a master degree. It was used the descriptive statistics (absolute and average frequency) and inferential (test of the significant qui-square the p = 0, 05). The results allowed identifying that the aging process was faced in a positive way, which was considered as a natural process in life, where they could imagine themselves as old and healthful individuals, and that take care of their own health to prepare for the elderly. The term gerontology is known by almost them all, which is understood as the study of aging process. The professors believe that the subject from the course do not contemplate this thematic, for preparing the academics in a general way and to do not have specific subjects. On this way, it is concluded that the expectations in regarding to the personal aging of professors are positive and they suggest the implantation of subjects in gerontology area in the course of physical Education.